Changes in lung function in children after pneumonia: a multicenter study - Hejun Jiang; Jingsheng Dai; Guifang Zhou; Guijun Yang; Liwen Zhang; Shuhua Yuan; Jing Zhang; Jiande Chen; Mingyu Tang; Jilei Lin; Li Li; Yufen Wu; et al. (Italian Journal of Pediatrics)
Abstract Background There are few studies on the changes in lung function after pneumonia in children. This study aims to explore the changes in lung function in children after pneumonia and analyze the risk factors for airway disorder, especially the impact of different pathogen infection on lung function. Methods This study collected data from patients who were hospitalized due to pneumonia in ten Chinese hospitals between January 2023 and December 2024. Pulmonary function tests were performed to assess changes in lung function one week and one month after discharge. Results A total of 566 children were included in this study, with 40.6% of patients still showing airway disorder one week after discharge. Different pathogenic infections had varying effects on pulmonary function. MP (Mycoplasma pneumoniae) infection [OR (95%CI): 1.881(1.268–2.789), P = 0.001] and RhV (rhinovirus) infection [OR (95%CI): 2.402(1.027–5.621), P = 0.043] were significant risk factors for the occurrence of SAD (Small Airway Disorder) one week after discharge. Male gender [OR (95%CI): 2.219, P = 0.001] and MP infection [OR (95%CI): 1.681(1.024–2.761), P = 0.039] were significant risk factors for the occurrence of LAD (Large Airway Disorder) one week after discharge. No positive pathogen results [OR (95%CI): 0.366(0.168–0.800), P = 0.011] were significant protective factors for the persistence of SAD one month after discharge, while RhV infection [OR (95%CI): 7.286(0.802, 66.238), P = 0.077] and lung consolidation [OR (95%CI): 1.753(0.956, 3.214), P = 0.069] showed mild significance for the persistence of SAD one month after discharge. Male gender [OR (95%CI): 2.246(1.137–4.436), P = 0.019] and RhV infection [OR (95%CI): 1.967(1.630–237.549), P = 0.019] were significant risk factors for the persistence of LAD one month after discharge, while no positive pathogen results [OR (95%CI): 0.249(0.092–0.678), P = 0.006] were a significant protective factor. Conclusions Approximately 40.6% of children after pneumonia still had airway disorder one week after discharge, which was closely related to different pathogenic infections. Patients with RhV pneumonia, in particular, should be closely monitored for changes in lung function after discharge.